2004
DOI: 10.1177/1524838004269487
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Culture and Minority Status on Women’s Experience of Domestic Violence

Abstract: The influence of culture and ethnic background on women's experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women's experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
208
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(216 citation statements)
references
References 51 publications
4
208
1
3
Order By: Relevance
“…The different racial-ethnic compositions of the two study samples and statistical power may explain the discrepant findings. The findings of this study are consistent with theoretical arguments indicating that immigrants may be at greater risk for IPV and thus IPSV 18,20,49,50 and research pertaining to mixed racial/ethnic samples that found foreign-born women were more likely to be victims of intimate partner femicide. 51,52 Since the majority of immigrants in the USA are from Latin America, 53 more studies are needed to examine the influence of nativity on IPV including IPSV among Latinas.…”
Section: Discussionsupporting
confidence: 88%
“…The different racial-ethnic compositions of the two study samples and statistical power may explain the discrepant findings. The findings of this study are consistent with theoretical arguments indicating that immigrants may be at greater risk for IPV and thus IPSV 18,20,49,50 and research pertaining to mixed racial/ethnic samples that found foreign-born women were more likely to be victims of intimate partner femicide. 51,52 Since the majority of immigrants in the USA are from Latin America, 53 more studies are needed to examine the influence of nativity on IPV including IPSV among Latinas.…”
Section: Discussionsupporting
confidence: 88%
“…Other factors, such as experiences of abuse may play a role. Not only the prevalence of abuse, but also the impact of abuse on mental health might vary between native and non-native pregnant women [14]. If the impact of abuse on mental health varies for natives and non-natives this should have implications for care.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies exist providing the prevalence and impact of IPV among ethnic minority groups, without investigating if ethnic background influenced the impact of violence [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…Physicians need to know what abused older African American women think about their physician's role in assisting them, given the higher likelihood that these older adults may lack trust in healthcare systems. (27) Lack of trust also may have an impact on who they perceive as a source of help for FV; these women may report obstacles to seeking help that are different from older Caucasian women or younger African American women. To begin to fill in these gaps in knowledge, we undertook a qualitative inquiry of experiences of older African American women affected by FV.…”
Section: Introductionmentioning
confidence: 99%